Analisis Sentimen Program Migrasi TV Digital Menggunakan Algoritma Naive Bayes dengan Chi Square - Virgaria Zuliana; Garno Garno; Iqbal Maulana (Jurnal informasi dan komputer, 2022)
Currently, television occupies the number 2 position as a source of information after social media. The analog TV broadcast system will be replaced with digital TV based on a plan issued by the Ministry of Communication and Information in Indonesia. Social media is useful for sharing thoughts and opinions about events, products and more, for example on the ongoing digital TV migration. The advantages of digital TV include superior technology and clear, crisp picture clarity. Some people argue that they are satisfied with the transition to digital TV, while others are the opposite. So that researchers are interested in these two opinions and are interested in analyzing public sentiment regarding the migration program for digital TV broadcasts on Twitter social media because of these two responses. The Naive Bayes method with Chi Square feature selection is used in the research process to examine differences in public opinion about migration to digital TV broadcasts. The results of the classification with 191 positive sentiment data and 185 negative sentiment data resulted in 96% accuracy, 93% precision and 100% recall.